Development of bacterial resistance induced by low concentration of two-dimensional black phosphorus via mutagenesis. Issue 25 (30th May 2022) - Wang, Huixiang; Fang, Fang; Deng, Chengxun; Zhu, Chengzhu; Yu, Zhimin; Liu, Xiaowei
Abstract : The wide use of nano-antibacterial materials has triggered concerns over the development of nanomaterials-associated bacterial resistance. Abstract : The wide use of nano-antibacterial materials has triggered concerns over the development of nanomaterials-associated bacterial resistance. Two-dimensional (2D) black phosphorus (BP) as a new class of emerging 2D nanomaterial has displayed excellent antibacterial performance. However, whether bacteria repeatedly exposed to 2D BP can develop resistance is not clear. We found that wild type E. coli K-12 MG 1655 strains can increase resistance to 2D-BP nanosheets after repeated exposure with subinhibitory concentration of 2D-BP nanosheets. Adaptive morphogenesis including the reinforced barrier function of cell membrane were observed in the resistant bacteria, which enhanced the resistance of bacteria to 2D-BP nanosheets. The whole-genome sequencing analysis showed that the three mutation genes including dmdA, mntP, and gyrA genes were observed in the 2D-BP resistant strains, which controlled catabolism, membrane structure, and DNA replication, respectively. Furthermore, transcriptional sequencing confirmed that these genes related to metabolization, membrane structure, and cell motility were upregulated in the 2D-BP resistant bacteria. The development of resistance to 2D-BP in bacteria mainly attributed to the changes in energy metabolism and membrane structure of bacteria caused by gene mutations. In addition, the up-regulated function of cell motility also helped the bacteria to develop resistance by escaping external stimuli. The results provided new evidence for understanding an important effect of nano-antibacterial materials on the development of bacterial resistance.